(untitled) (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
This study aims to formulate or steps to produce a primus inter pares leader in the midst of a flawed democracy and to find out what factors hinder the birth of a primus inter pares leader from the electoral democracy process. The research method used is a descriptive qualitative research method through a case study approach. In determining the informants in the study, the researcher used a purposive technique. The data collection technique chosen was using observation, interviews, Focus Group Discussions (FGD), documentation checking the validity of the data using triangulation techniques. The results of the study are the formulation or steps to produce a primus inter pares leader in the midst of a flawed democracy and the factors that hinder the birth of a primus inter pares leader from the electoral democracy process are formulated aspects of the study and problems in realizing quality leader candidates, namely the problems of political parties, oligarchy, corruption and the rationality of society. In the aspect of political parties, a good party for the interests of society is called Good Political Party Governance which is able to provide a clear path for future leaders, who understand the values ​​of democracy, integrity, and public service.